Genre Analysis of The Message Segments of An Indonesian-English Tourism Text Translation: Case in Madura - Masduki Masduki; Misnadin Misnadin (Makassar State University, 2022)
Abstract. Genre as a spectrum of textual manifestation signals its textual presence through linguistic devices. In the tourism text, the signal of its presence is marked by a transition from one movement or organizing activity to another. Translating genre is central to the work of translators. The fact is the translation process often does not take one line and translators often overlook the role of contextual specifications. This difficulty is also compounded by the fact that the readers’ understanding when reading the translation text often has difficulty in obtaining the meaning. Therefore, the purpose of this study is to identify and explain the translation of an Indonesian-English tourism text genre focusing on message segments to determine the moves and rhetorical functions of the discourse structure and how they may contribute to the readability of the text. The study was descriptive qualitative research. The data was extracted from a variety of documents related to Madura tourism. The data collection technique was document review and the data analysis was interactive model analysis. The results of the study showed that the message segments of the Indonesian-English tourism text translation were constructed with three moves (explanation, illustration, and argumentation) and three rhetorical functions (description, definition, and cause and effect). These moves and rhetorical functions in the translation of the Indonesian-English tourism text genre contributed to the results of the readability of the translated texts, i.e., they were fully comprehensible without unnecessary effort in the part of the readers. The findings suggest that genre analysis of the message segments of the tourism text translation can be a good alternative for communicating the intentions of the source texts. Thus, this can be a good practice for translators to consider when translating texts and other related texts as well.Keywords: Genre, Message Segment, Translation, Tourism